2013
DOI: 10.2527/jas.2012-5659
|View full text |Cite
|
Sign up to set email alerts
|

Piglet birth weight and litter uniformity: Effects of weaning-to-pregnancy interval and body condition changes in sows of different parities and crossbred lines1

Abstract: Piglet birth weight and litter uniformity were studied in sows of different parities and crossbred lines in relation to: 1) weaning-to-pregnancy interval (WPI) and 2) sow body condition changes (in BW and backfat thickness) during lactation and gestation in sows with a short WPI (≤7d). At the Institute for Pig Genetics (IPG) research farm, individual piglet birth weights and sow body condition (BW and backfat thickness at farrowing and weaning) were measured for 949 TOPIGS20 and 889 TOPIGS40 sows with >4 total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 29 publications
3
42
0
2
Order By: Relevance
“…And in a recent study in which primiparous sows nursing similar litter sizes were modestly feed restricted (7 kg feed/d versus recommended 8 kg feed/d) during lactation, high weight loss sows had greater loin muscle depth loss over lactation with subsequent reduced implantation sites and embryo viability at day 35 of gestation in comparison to low weight loss dams (Hoving et al, 2012). Wientjes et al (2013) reported that greater body weight and backfat thickness losses during lactation were associated with reduced litter uniformity in the subsequent farrowing as measured by piglet birth weight. Furthermore, sows with increased backfat gain during the subsequent gestation period were negatively associated with total number of piglets born.…”
Section: Discussionmentioning
confidence: 97%
“…And in a recent study in which primiparous sows nursing similar litter sizes were modestly feed restricted (7 kg feed/d versus recommended 8 kg feed/d) during lactation, high weight loss sows had greater loin muscle depth loss over lactation with subsequent reduced implantation sites and embryo viability at day 35 of gestation in comparison to low weight loss dams (Hoving et al, 2012). Wientjes et al (2013) reported that greater body weight and backfat thickness losses during lactation were associated with reduced litter uniformity in the subsequent farrowing as measured by piglet birth weight. Furthermore, sows with increased backfat gain during the subsequent gestation period were negatively associated with total number of piglets born.…”
Section: Discussionmentioning
confidence: 97%
“…Selection for litter size has been shown to disproportionally increase ovulation rate (OR) and prenatal mortality (Johnson et al, 1999;van der Waaij et al, 2010;Vallet et al, 2014) and OR of 25 to 30 are relatively common nowadays (Patterson et al, 2008;Wientjes et al, 2013). The increase in prenatal mortality with an increase in OR seems due to both an increase in pre-implantation and post-implantation mortality (van der Waaij et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Quesnel, 2009). Insufficient restoration of follicle development at weaning may increase developmental variation within the pre-ovulatory follicle pool, as may be deduced from the recently found negative and linear relation between sow body condition loss during lactation and subsequent litter uniformity (Wientjes et al, 2013). In a previous study, in which sows lost 12.0% 6 0.5% of their BW during lactation, plasma insulin concentrations during WEI were positively related to LH, follicle development and subsequent luteal and embryo development at day 10 of pregnancy (Wientjes et al, 2012b and2012c).…”
mentioning
confidence: 99%